The Important Role of Dimension in Human Resources Studies: The Curious Case of Employee Satisfaction - ‘Azzam, Muhammad Abdullah; Riani, Asri Laksmi; Aini, Intan Novela Qurrotul; Harsono , Mugi (The Eastasouth Management and Business, 2024)
Human resources studies are closely related with behavioral study and gained several scholarly attention Indonesia. But there is an important aspect, regarding how scholars use variables in their respective studies, the dimension of a variable is often forgotten. This article will try to shed light on this topic. by doing a thorough review of the case of the employee satisfaction variable. We will explore how the employee satisfaction variable is viewed, and how by looking at the dimension of this variable an entirely new perspective could be found on how this variable interacts with other variables, namely organizational commitment. We will look thoroughly at several studies, especially those that focused on the establishment of the dimension from this variable, and discuss the study's results., Then try to explain, how future research can utilize dimensions to gain a better understanding of human resources and behavioral studies.